Synthesis and Application of Monoazo Acid Dyes Containing Trifluoromethyl Group and Their Methyl Analogous on Polyamides - TELI, M.D.; Sekar, N.; Prabhu, K.H. (Asian Journal of Chemistry, 2010)
A new series of monoazo acid dyes containing m-trifluoromethyl aniline reacted with various couplers such as Schaeffer acid, N.W. acid, γ-acid and N-(4-sulphophenyl)-3-methyl-5-pyrazolone compound were prepared. These dyes were compared with parallel series of dyes obtained from m-toluidine in place of m-trifluoromethyl aniline. Subsequently the polyamide fabrics mainly silk, wool and nylon were dyed and their properties such as water repellency, colour depth and fastness properties were determined. Trifluoromethyl based dyes were found to impart improved water repellent properties without impairing any other conventional performance properties, significantly.